2013
DOI: 10.1039/c3ra23324c
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid films of reduced graphene oxide with noble metal nanoparticles generated at a liquid/liquid interface for applications in catalysis

Abstract: Free-standing ultra-thin hybrid films of reduced graphene oxide (rGO) with Au, Ag and Pd nanoparticles are generated at an aqueous/organic interface by in situ chemical reduction and spontaneous assembly.The reduction is initiated at a 'bare' interface or a 'modified' interface in a single step or two-step synthetic strategy. The hybrid materials are characterized by UV-visible, infra-red and Raman spectroscopies, X-ray diffraction, scanning electron (SEM), transmission electron (TEM) and atomic force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…100 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 26 the stirring or sonication procedure required to assemble the structure at the liquid/liquid interface or, alternatively, as a two-step process whereby the rGO film is formed at the interface prior to metal reduction. 101,102 The one step process was shown to produce a higher surface coverage. 102 rGO may be formed from GO by the same reducing reagent used to generate the metal nanoparticles in solution.…”
Section: Decorated Nanostructures and Compositesmentioning
confidence: 99%
“…100 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 26 the stirring or sonication procedure required to assemble the structure at the liquid/liquid interface or, alternatively, as a two-step process whereby the rGO film is formed at the interface prior to metal reduction. 101,102 The one step process was shown to produce a higher surface coverage. 102 rGO may be formed from GO by the same reducing reagent used to generate the metal nanoparticles in solution.…”
Section: Decorated Nanostructures and Compositesmentioning
confidence: 99%
“…28 Furthermore, the employment of easily processable, liquid-phase exfoliated, reduced graphene oxide (rGO) materials to support deposition of noble metals at the organic/water interface has been widely investigated, mainly to prepare GR-based catalysts or electrode materials on solid substrates. 3,6,22,24,[29][30][31][32] The use of CVD GR offers a macroscopic material-visible to the naked eye-that has not been deliberately oxidized and consists of a high-quality, well-defined monolayer, as opposed to liquid-phase exfoliated rGO aggregates. 27 Functionalization of a free-standing CVD GR monolayer with noble metal (Au, Pt, Pd) nanoparticles, using a low-cost, two-step, solution chemistrybased process has been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial polymerisation of polypyrrole (PPy) and polyaniline (PANI) at the non-polarised, chloroform/water interface using ferric chloride (FeCl 3 ) as oxidant was reported in 2008 [28], and thereafter several papers described preparation of CPs at the liquid/liquid interface [29][30][31][32][33]. Numerous studies have also reported the formation of adsorbed carbon nanomaterial films via self-assembly, such as CNTs, and adsorbed films of few-layer GR or reduced graphene-oxide (rGO) at non-polarised, liquid/liquid interfaces, often with the specific aim of preparing transparent or modified carbon-coated electrode materials [34][35][36][37]. Recently we have extended this approach to the localisation and moreover the functionalisation of CVD GR at the ITIES [38,39].…”
Section: Introductionmentioning
confidence: 98%